Os ganhos sociais decorrentes da interiorização laboral de mulheres venezuelanas no Brasil - Pachioni, Miguel Sgarbi (2023)
The present decade is characterized by the expressive and continuous forced movement of people as a result of armed conflicts, violation of human rights and persecutions of different natures. In Brazil, the arrival of people as refugees has intensified since 2017, especially Venezuelans – who represent about 80% of recognized refugees. As a humanitarian response to the issue, the Brazilian federal government structured in 2018 the Welcome Operation, centered on three pillars: border planning and documentation; shelter and humanitarian assistance; and voluntary interiorization. In March 2023, more than 100,000 people were transferred from Boa Vista/RR and Manaus/AM to approximately 950 Brazilian municipalities, in four different modalities. Among these, the “Signaled Job Vacancy” (VES) promotes the employability of Venezuelan professionals hired, but does this factor itself guarantee the local integration of their family members? The case study carried out through virtual interviews with three employed Venezuelan women uses process tracing to assess the consequences of their employability as a central element for the labor reintegration of other family members, seeking to understand to what extent the formal employment of a Venezuelan woman interiorization enables social gains from their close network – even if job opportunities are below their capabilities, they build sustainable family planning by strengthening the protective structure, increasing income and facilitating access to services and rights